1983
DOI: 10.1042/cs0650533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxia and Hypercapnic Acidosis on Renal Autoregulation in the Dog: Role of Renal Nerves

Abstract: Previous studies suggest that hypoxia and hypercapnic acidosis exert a renal nerve mediated adverse effect on renal haemodynamic function. We therefore examined the effect of hypoxia and hypercapnic acidosis on renal blood flow and glomerular filtration rate responses to lowering renal perfusion pressure from 125 to 75 mmHg in the anaesthetized dog. To study the role of renal nerves in these responses, paired innervated and denervated kidneys were studied in each animal. Hypoxia (PO2 43 +/- 3 mmHg) affected ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The changes in RBF observed in our experiments can thus be due to a direct stimulation of the renin-angiotensin system by hypercapnia, or to a stimulation via the renal nerves as suggested by different authors (7,12,13,15,20).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The changes in RBF observed in our experiments can thus be due to a direct stimulation of the renin-angiotensin system by hypercapnia, or to a stimulation via the renal nerves as suggested by different authors (7,12,13,15,20).…”
Section: Discussionsupporting
confidence: 57%
“…The PAH extraction values were comparable to those observed in normocapnic animals, thus demonstrating that hypercapnia does not change PAH extraction, and that the drop in C PAH corresponds to a true decrease in RBF. A 10% decrease in PAH extraction was observed by Anderson et al (11,12) during hypercapnic acidosis in dogs, but was apparently not found in other studies ofthe same group (13,14), nor was any change in PAH extraction HEIJDEN AND GUIGNARD during hypercapnia mentioned by Norman et al (7) and by Berns et al (15). This is in agreement with studies using either a sine wave electromagnetic flowmeter (6) or microspheres (4,5) for measuring RBF.…”
Section: Discussionmentioning
confidence: 79%
“…Anderson et al 47 reported that hypercapnic acidosis can decrease renal blood flow and GFR during the period when renal perfusion pressure decreases from 125 to 75 mm Hg. The amount of acidosis reached in that study (pH 7.03 ± 0.01) was more extreme than in the study reported here during anesthesia (pH 7.18 ± 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…For example, systemic hypoxia has been reported to induce antidiuresis and antinatriuresis in anaesthetized dogs (Anderson et at. 1978;Bruns, 1978;Anderson, Pluss, Pluss, Bell & Zerbe, 1983), fetal lambs (Nakamura, Ayres, Gomez & Robillard, 1985), unanaesthetized rats (Behm, Mewes, DeMuinck Keizer, Unger & Rettig, 1993), and some human subjects (Honig, 1989). In contrast, diuresis and natriuresis has been reported in unanaesthetized dogs and anaesthetized rats (Walker, 1982;Rose, Althaus, Kaiser, Miller & Carey, 1983;Colice, Yen, Ramirez, Dietz & Ou, 1991) and in humans (Ullman, 1961;Koller, Buhrer, Felder, Schopen & Vallotten, 1991).…”
mentioning
confidence: 99%